Exacerbation of Brain Injury by Post-Stroke Exercise Is Contingent Upon Exercise Initiation Timing - Li, Fengwu; Geng, Xiaokun; Khan, Hajra; Pendy Jr., John T.; Peng, Changya; Li, Xiaorong; Rafols, Jose A.; Ding, Yuchuan (Frontiers in Cellular Neuroscience, 2017)
Accumulating evidence has demonstrated that post-stroke physical rehabilitation may reduce morbidity. The effectiveness of post-stroke exercise, however, appears to be contingent upon exercise initiation. This study assessed the hypothesis that very early exercise exacerbates brain injury, induces reactive oxygen species (ROS) generation, and promotes energy failure. A total of 230 adult male Sprague-Dawley rats were subjected to middle cerebral artery (MCA) occlusion for 2 h, and randomized into 8 groups, including 2 sham injury control groups, 3 non-exercise and 3 exercise groups. Exercise was initiated after 6 h, 24 h, and 3 days of reperfusion. Twenty-four hours after completion of exercise (and at corresponding time points in non-exercise controls), infarct volumes and apoptotic cell death were examined. Early brain oxidative metabolism was quantified by examining ROS, ATP, and NADH levels 0.5 h after completion of exercise. Furthermore, protein expressions of angiogenic growth factors were measured in order to determine whether post-stroke angiogenesis played a role in rehabilitation. As expected, ischemic stroke resulted in brain infarction, apoptotic cell death and ROS generation, and diminished NADH and ATP production. Infarct volumes and apoptotic cell death were enhanced (p < 0.05) by exercise that was initiated after 6 h of reperfusion, but decreased by late exercise (24 h, 3 days). This exacerbated brain injury at 6 h was associated with increased ROS levels (p < 0.05), and decreased (p < 0.05) NADH and ATP levels. In conclusion, very early exercise aggravated brain damage, and early exercise-induced energy failure with ROS generation may underlie the exacerbation of brain injury. These results shed light on the manner in which exercise initiation timing may affect post-stroke rehabilitation.